Reader-friendly reports : a no-nonsense guide to effective writing for MBAs, consultants, and other professionals - Daniel, Carter A., 1938-2013 (McGraw-Hill, 2012)
An A to Z guide to ensuring you meet your first priority: making sure people can understand and remember your report from beginning to end; this book gives you everything you need to translate your hard-won figures; conclusions; and insights into concise and powerful reports. --